2011
DOI: 10.1182/blood-2010-07-299099
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E receptor 2 is involved in the thrombotic complications in a murine model of the antiphospholipid syndrome

Abstract: Antiphospholipid (aPL)/anti-␤ 2 glycoprotein I (anti-␤ 2 GPI) antibodies stimulates tissue factor (TF) expression within vasculature and in blood cells, thereby leading to increased thrombosis. Several cellular receptors have been proposed to mediate these effects, but no convincing evidence for the involvement of a specific one has been provided. We investigated the role of Apolipoprotein E receptor 2 (ApoER2) on the pathogenic effects of a patient-derived polyclonal aPL IgG preparation (IgG-APS), a murine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
109
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 48 publications
(58 reference statements)
3
109
0
Order By: Relevance
“…The interaction of dimerized β2GP1 with either ApoER2' or GPIbα was found to lower the threshold of platelet activation by collagen or fibronectin surfaces [31,65]. While EC and monocytes do not express ApoER2', other members of LDL-receptor family were shown to bind the dimerized form of β2GP1 [64,66].…”
Section: Apoer2'and Gpibα As Apla Receptorsmentioning
confidence: 98%
See 1 more Smart Citation
“…The interaction of dimerized β2GP1 with either ApoER2' or GPIbα was found to lower the threshold of platelet activation by collagen or fibronectin surfaces [31,65]. While EC and monocytes do not express ApoER2', other members of LDL-receptor family were shown to bind the dimerized form of β2GP1 [64,66].…”
Section: Apoer2'and Gpibα As Apla Receptorsmentioning
confidence: 98%
“…Several candidate receptors have been proposed for aPLA: in vivo studies have shown that deficiencies of TLR4 [29], Annexin A2 [30], ApoER2 [31] and several complement factors [20] reduced the pathogenic effects of aPLA. Moreover, ex vivo studies suggest a role for TLR2 [32][33][34], CD14 [34], GPIbα [35] and TLR8 [36] in aPLA-activated monocytes and EC.…”
Section: Candidate Receptors For Aplamentioning
confidence: 99%
“…Additionally, a recombinant-binding domain I of ApoER2 has been shown to act as an inhibitor of increased thrombus formation in different murine models of APS. Moreover, aPL-induced increases in leucocyte adhesion to endothelium, peritoneal macrophage TF activity/expression and thrombus formation were significantly reduced in ApoER2 (À/À) mice (Urbanus et al, 2008b;Romay-Penabad et al, 2011). Interestingly, ApoER2′ needs a receptor cooperation for its optimal function and specificity.…”
Section: Open Questionsmentioning
confidence: 99%
“…However, in vitro and in vivo experimental models highlight that TLR4 only partially contributes to the thrombogenic effect of aPL, suggesting that more than one receptor may be involved in b2GPI cellular binding. The main candidate receptors for b2GPI on cell membranes have been identified as TLR2, megaline, apolipoprotein Ereceptor2′ (ApoER2′), glycoprotein Iba (GPIba) and platelet factor 4 (PF4) (Kobayashi Review ª 2013John Wiley & Sons Ltd et al, 2001Shi et al, 2006;Alard et al, 2010;Sikara et al, 2010;Romay-Penabad et al, 2011).…”
Section: Open Questionsmentioning
confidence: 99%
“…The role of apoER2' was recently investigated in an animal model of thrombosis. Passive immunization of apoER2'-/-mice with aPL purified from patients or monoclonal anti-2GPI or 2GPI chimeric dimers, caused significantly reduced clots and reduced TF expression of vascular cells and macrophages, compared with immunization of control mice [ 86 ]. The role of GPIba as a 2GPI-receptor and potential mediator of platelet activation has been studied by in vitro binding assays and selective inhibition using specific antibodies [ 87 ].…”
Section: A S E C O N D I N D I C a T I O N O F I M P A I R E D P L A mentioning
confidence: 99%